X-ray detector requirements for laser–plasma accelerators - Armstrong, Chris D.; Scott, G. G.; Richards, S.; Patel, J. K.; Fedorov, K.; Gray, R. J.; Welsby, K.; Rajeev, P. P. (Frontiers in Physics, 2023)
Laser–plasma interactions (LPIs) are an emerging source of a range of energetic radiation. LPI experiments drive ultra-short (< ps) and brilliant sources of X-rays from keV to MeV energies. Designing detectors to maximise the sensitivity and resolution achievable with these sources is paramount to optimising laser-driven accelerators. In this article, we explore the key parameters associated with laser-driven X-ray sources and the detector systems required to characterise them. We present a concise approach to modelling the sensitivity and resolution for indirect detector systems factoring in both the optical collection and the X-ray attenuation within the scintillator.